2014
DOI: 10.1093/eurpub/cku062
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent ecstasy use and depression: cause and effect, or two outcomes of home environment?

Abstract: Ecstasy use during adolescence may be associated with poorer mental health; however, this association can be explained by the confounding social influence of family dynamics. These findings could be used to aid effective evidence-based drug policies, which concentrate criminal justice and public health resources on reducing harm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…Our effect estimates are smaller and weaker compared to some studies with larger samples (e.g. McCann, Higgins, Perra, McCartan, & McLaughlin, 2014), but these used cross-sectional designs and non-childhood attachment measures. Without access to rich data on parental and environmental variables, these studies also lack potentially relevant confounders, which our study was able to adjust for.…”
Section: Comparison With Literaturecontrasting
confidence: 94%
“…Our effect estimates are smaller and weaker compared to some studies with larger samples (e.g. McCann, Higgins, Perra, McCartan, & McLaughlin, 2014), but these used cross-sectional designs and non-childhood attachment measures. Without access to rich data on parental and environmental variables, these studies also lack potentially relevant confounders, which our study was able to adjust for.…”
Section: Comparison With Literaturecontrasting
confidence: 94%
“…Traumatic events and childhood depression were both correlated with psychedelic use and were both strong predictors of all indicators of mental health problems. It would be preferable to have a data set with data on both exposure to traumatic events and childhood depression, as well as other risk factors, such as history of childhood abuse, and family history of mental illness (McCann et al, 2014; Proal et al, 2014). Note, a study of 52 people hospitalized for first psychotic episode shortly after LSD use found that they had elevated rates of parental psychiatric hospitalization, similar to people with schizophrenia (Vardy and Kay 1983).…”
Section: Limitationsmentioning
confidence: 99%
“…Modelling based on the social network data also found evidence that cross-sectional data can be used to estimate peer effects on cannabis use [ 33 ]. Other recent findings indicate that while ecstasy use during adolescence may be associated with poorer mental health, the association can be explained by the confounding social influence of family dynamics [ 34 ]. The BYDS data have also allowed for the investigation of ecstasy use within a peer/school context.…”
Section: Resultsmentioning
confidence: 99%